The Role of Market Orientation in Improving the Financial Performance of Travel Agencies - Abbasgholi Sangi Nour Pour (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2018)
The purpose of this study was to investigate the effect of market orientation on financial performance and the mediating role of customer satisfaction and loyalty. A conceptual model has been used to establish the hypotheses. Data were collected by random cluster sampling from 196 employees of active travel agencies in North West of Iran. Data have been tested using Structural Equation Modeling. The results indicate the positive impact of market orientation on financial performance. Also, the findings support the mediating role of loyalty between customer satisfaction and financial performance. However, there are no solid reasons for the mediating role of customer satisfaction between market orientation and financial performance. Testing the suggested research model for the first time in the targeted community is considered an innovative aspect. Suggestions presented to managers of travel agencies, as well as future researchers.